CHICKEN SOUP FOR THE SOUL LOVE STORIES - Canfield, Jack (Health Communications, Inc., 2008)
Whether it is at first sight, develops over time with a close friend, or it hits you like a ton of bricks--falling in love is a lyrical life-changing event. Chicken Soup for the Soul® Love Stories will transport you to the moments of your life that were filled with devotion and unconditional love. Who can forget what it feels like to walk on air, share private jokes, and ponder over intimate moments? This collection of stories is sure to rouse the inner romantic in your heart, with stories of long-lost love rekindled in the twilight of life, young love discovered, and love that truly lasts forever. But this book will also remind you of the everlasting love between friends, family, and parents and children. Stories peppered throughout celebrate the vastness of love in all its many forms, including the story of one woman who is able to endure a painful illness because of the unconditional love and affection she receives from her cat, and the story about the love shared between father and daughter when he returns from overseas, as well as stories about love found in surprising ways by women and men who thought their time for romantic love had passed. Chicken Soup for the Soul Love Stories will take you back to your most cherished memories and inspire you to create a few more.